2018
DOI: 10.1371/journal.pone.0208545
|View full text |Cite
|
Sign up to set email alerts
|

Coral-dwelling fish moderate bleaching susceptibility of coral hosts

Abstract: Global environmental change has the potential to disrupt well established species interactions, with impacts on nutrient cycling and ecosystem function. On coral reefs, fish living within the branches of coral colonies can promote coral performance, and it has been hypothesized that the enhanced water flow and nutrients provided by fish to corals could ameliorate coral bleaching. The aim of this study was to evaluate the influence of small, aggregating damselfish on the health of their host corals (physiology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 74 publications
2
46
0
Order By: Relevance
“…A new long-term study of ecosystem impacts shows that severe bleaching persistently changes reef fish communities, lasting for more than 15 yrs (Robinson et al 2019). Other novel work indicated that fish living within the branches of corals may moderate the impacts of bleaching on their hosts (Chase et al 2018).…”
Section: What Have We Learned From Gcbe-3?mentioning
confidence: 99%
“…A new long-term study of ecosystem impacts shows that severe bleaching persistently changes reef fish communities, lasting for more than 15 yrs (Robinson et al 2019). Other novel work indicated that fish living within the branches of corals may moderate the impacts of bleaching on their hosts (Chase et al 2018).…”
Section: What Have We Learned From Gcbe-3?mentioning
confidence: 99%
“…Damselfishes (Pomacentridae) are the most diverse family of planktivorous fishes on the GBR and can be extremely abundant [3]. While consumption of zooplankton by planktivorous damselfishes contributes to nutrient transfer onto reef environments, these fishes may also provide more indirect ecological benefits: some eat the larvae of coral-feeding crown-of-thorns starfish, possibly constraining starfish population upsurges [4] and associated coral declines, while others that preferentially reside within corals may moderate the bleaching susceptibility of their coral hosts [5]. Additionally, planktivorous damselfishes are a primary source of food for many predatory fishes on the GBR including the commercially important coral trout (Plectropomus spp.)…”
Section: Introductionmentioning
confidence: 99%
“…These hotspots, areas of high localized nutrient production by fishes [28,102] are generally infrequent across seascapes. Nutrient subsidy, along with other fish-derived services like increased photosynthesis [103], colony growth [28], bleaching susceptibility [27] sediment removal [101], may be density-dependent (i.e., >15 g seen in studies focusing on larger-bodied or more abundant fish species, see [26,104,105]) and fish-species dependent. With 68% of corals vacant, it is clear that many colonies do not receive potential beneficial effects of resident damselfish.…”
Section: Discussionmentioning
confidence: 99%
“…For colonies with resident fishes (n = 142), the numbers of all fishes on each focal colony were recorded, and all fish were placed into general standard-length size classes of small, medium, and large, for each species respectively. Size class data were subsequently converted into biomass estimates, based on published length/weight relationships generated from damselfish [27,47], where damselfish were collected using hand-nets and a liquid anesthetic (a diluted solution of clove oil, ethanol, and seawater [27,59,60]). Surveys focused on ecologically important damselfish's occupancy and biomass patterns rather than fish numbers, as biomass has been directly linked to fish-derived services and benefits for corals [26,61].…”
Section: Colony Diametermentioning
confidence: 99%
See 1 more Smart Citation